Relationship of Occupational Accidents to K3 Knowledge, K3 Training, and Use of Personal Protective Equipment in the Welding Process - Muhammad Firdaus Bin Yusup (Collaborate Engineering Daily Book Series, 2023)
The rapid development of science and technology provides convenience in the industrial world, such as increasing work productivity and the number of workers. However, the development of technology has problems, one of which is the problem of occupational safety and health which can cause harm to workers and companies. Often, welders neglect personal protective equipment, which can result in work accidents when welding. Therefore, this research was conducted to determine the relationship between occupational accidents and OSH knowledge, OSH training, and the use of personal protective equipment in the welding process. The method used is univariate and bivariate analysis. The results showed a significant relationship between K3 knowledge and occupational accidents in the welding process (sig. 0.001 <0.005). At the same time, there was no significant relationship between K3 training (sig. 0.235 value > 0.005) and the use of PPE (sig. 0.187 > 0.005) with work accidents in the welding process.